Influência do tipo de alimento sobre o estabelecimento de Haemonchus contortus em cordeiros - Carvalho, Nadino [UNESP] (2014)
The aim of this study was evaluate the effect of diet and immunity on the establishment of Haemonchus contortus in lambs. The trial was in a 2 x 2 factorial design, using two diets (hay or hay+concentrate) and two immune states (normal or supressed). The animals were randomly in four experimental groups (n = 7): hay suppressed, hay normal, hay+concentrate suppressed and hay+concentrate normal. The hay was of Cynodon dactylon (CV Coast cross) and will concentrate offered equivalent to 3% by weight, with weekly adjustments amount. Immunosuppression was performed four hours before artificial infection and repeated weekly, Methylprednisolone was used at a dose 1.33 mg/kg bodyweight (intramuscular) The adaptation period to the diet was 22 days. Each lamb received 4,000 infective larvae (L3) of H. contortus. Haematological, performance, immune response weekly and fecal egg count (FEC) at 21, 24 and 27 days after infection were evaluate. The animals were slaughter 28 days after infection, and the parasites recovered were quantified and measured the length and number of eggs in females were counts. Means were compare by analysis of variance at 5 % significance (Tukey´s test). The worm burden was similar in both groups, however the FEC was lower in all samples on animals that received hay+concentrate (P < 0.05). The immunosuppressive was effective on reduce the IgG plasma levels and number of abomasal mucosal mast cell and eosinophils, however there was little favouritism to parasite against immunosuppression, which favoured only in the size of male parasites ( P < 0.05). The greater daily weight gain was observed in animals receiving concentrate, however the group hay+concentrate normal showed higher weight gains than hay+concentrate suppressed group (P < 0.05). The supply of concentrate does not exercise direct effect on establishment of H. contortus. Supplementation favours weight gain, lessens the pathogenic effects of the parasite and leads ...